The roles of nuclear myosin in the DNA damage response. (9th October 2020) - Cook, Alexander W; Toseland, Christopher P
Abstract: Myosin within the nucleus has often been overlooked due to their importance in cytoplasmic processes and a lack of investigation. However, more recently, it has been shown that their nuclear roles are just as fundamental to cell function and survival with roles in transcription, DNA damage and viral replication. Myosins can act as molecular transporters and anchors that rely on their actin binding and ATPase capabilities. Their roles within the DNA damage response can varies from a transcriptional response, moving chromatin and stabilizing chromosome contacts. This review aims to highlight their key roles in the DNA damage response and how they impact nuclear organization and transcription. Graphical Abstract: